Gossypiboma masquerading as nephrocutaneous fistula - Pandey, Siddharth (BMJ Case Rep, 2018)
Nephrocutaneous fistula is a rare complication of surgical procedures involving the kidney. Fistula formation is also a complication seen in gossypiboma. We present the case of a patient who was initially suspected to have nephrocutaneous fistula after open pyelolithotomy. Later while undergoing open resection of fistula, he was found to have a retained surgical sponge (gossypiboma) near the lower pole of kidney. Gossypiboma is a term used for mass formed around a surgical sponge accidentally left in the body. It is most of the times not diagnosed by radiological imaging and thus results in unnecessary investigations to rule out other causes for the patient’s symptoms. Having a high index of suspicion may lead to an earlier diagnosis. But the prevention of gossypiboma is of the utmost importance. A meticulous approach while operating by the surgeon and operating rooms staff is very important in doing so.